2021
DOI: 10.1139/cjc-2019-0485
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reaction kinetics and mechanism of bisphenol A with K2S2O8 in aqueous solution: a laser flash photolysis study

Abstract: The photochemical reaction kinetics and mechanism of bisphenol A (BPA) with potassium persulfate (K2S2O8) were investigated by using 266 nm laser flash photolysis and gas chromatography mass spectrum (GC-MS) technique. Sulfate radical (SO4•–), generated upon K2S2O8 photolysis, reacted with BPA with the overall rate constant of (1.61±0.15)×109 L mol-1 s-1, and two main reaction mechanisms were involved. One was addition channel to generate BPA–SO4•– adduct with a specific second-order rate constant of (1.09±0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The detection of normalSO 4 was achieved by direct monitoring at its feature wavelength, 450 nm ( ε = 1650 M –1 cm –1 ), and N ( normalSO 4 ) 0 was derived from the maximum absorbance. Figure c (red line) showed that after the excitation, the maximal absorbance can increase to 0.044, and the initial concentration of produced normalSO 4 was then determined to be 26.6 μM (Figure c, inset red line).…”
Section: Resultsmentioning
confidence: 99%
“…The detection of normalSO 4 was achieved by direct monitoring at its feature wavelength, 450 nm ( ε = 1650 M –1 cm –1 ), and N ( normalSO 4 ) 0 was derived from the maximum absorbance. Figure c (red line) showed that after the excitation, the maximal absorbance can increase to 0.044, and the initial concentration of produced normalSO 4 was then determined to be 26.6 μM (Figure c, inset red line).…”
Section: Resultsmentioning
confidence: 99%
“…In the pristine state, no specific signal was observed for the composite films of all three binders. After the first charging process, however, the peak near 300 nm, ascribed [ 32 ] to the sulfate‐derived radical, was observed only for the CRN‐based composite film (Figure S22a, Supporting Information), unlike its ALG‐ and PVDF‐based counterparts (Figure S22b,c, Supporting Information). This sulfate‐derived radical reacts with the Lewis acidic PF 5 decomposed from the anion of the lithium salt (Figure S21a, Supporting Information) to form the LiSO 4 PF 5 − intermediate ( m / z = 228.93) as detected by ToF‐SIMS (Figure S23a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%